2017
DOI: 10.1214/16-aos1457
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood-based model selection for stochastic block models

Abstract: The stochastic block model (SBM) provides a popular framework for modeling community structures in networks. However, more attention has been devoted to problems concerning estimating the latent node labels and the model parameters than the issue of choosing the number of blocks. We consider an approach based on the log likelihood ratio statistic and analyze its asymptotic properties under model misspecification. We show the limiting distribution of the statistic in the case of underfitting is normal and obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
159
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(165 citation statements)
references
References 32 publications
(46 reference statements)
0
159
0
Order By: Relevance
“…This first group of methods includes a variety of regu- [20] Minimum description length MDL (DC-SBM) [20] Minimum description length S-NB [9] Spectral with non-backtracking matrix S-cBHm [11] Spectral with Bethe Hessian, version m S-cBHa [11] Spectral with Bethe Hessian, version a AMOS [32] Statistical test using spectral clustering LRT-WB (DC-SBM) [13] Likelihood ratio test larization approaches for choosing the number of communities, e.g., those based on penalized likelihood scores [8], [28], various Bayesian techniques including marginalization [7], [29], cross-validation methods with probabilistic models [15], [17], compression approaches like MDL [20], and explicit model comparison such as likelihood ratio tests (LRT) [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This first group of methods includes a variety of regu- [20] Minimum description length MDL (DC-SBM) [20] Minimum description length S-NB [9] Spectral with non-backtracking matrix S-cBHm [11] Spectral with Bethe Hessian, version m S-cBHa [11] Spectral with Bethe Hessian, version a AMOS [32] Statistical test using spectral clustering LRT-WB (DC-SBM) [13] Likelihood ratio test larization approaches for choosing the number of communities, e.g., those based on penalized likelihood scores [8], [28], various Bayesian techniques including marginalization [7], [29], cross-validation methods with probabilistic models [15], [17], compression approaches like MDL [20], and explicit model comparison such as likelihood ratio tests (LRT) [13].…”
Section: Methodsmentioning
confidence: 99%
“…• Bayesian marginalization and regularized likelihood 3 approaches [6], [7], [8], • information theoretic approaches [12], • modularity based methods [5], • spectral and other embedding techniques [9], [10], [11], [60], [63], • cross-validation methods [14], [15], and • statistical hypothesis tests [13]. We note, however, that the boundaries among these classes are not rigid and one method can belong to more than one group.…”
Section: Appendix E Model Selection Approachesmentioning
confidence: 99%
“…The second is the increasing adopting of the DC-SBM (Karrer and Newman, 2011), not only in modifying the model, but also in aiding model selection in different ways (Yan et al, 2014, Yan, 2016, Wang and Bickel, 2017, Hu et al, 2019. While it is particularly useful for dealing with the degree heterogeneity, the results are more mixed when it is applied to real-world networks, as seen in Section 8.…”
Section: Discussionmentioning
confidence: 99%
“…Yan (2016) presented a mixed picture in which the DC-SBM always dominated the original SBM, even more so at smaller K, but the ICL criterion actually increased with K, thus potentially requiring some penalty. While Wang and Bickel (2017) selected K = 4 using their penalised log-likelihood, closer investigation revealed that one ground-truth group matched well with one inferred group, while the other ground-truth group is split into three smaller inferred groups. However, Hu et al (2019) found that, at a certain value of the tuning parameter λ (Section 7.1) the penalised loglikelihood selected K = 1, therefore arguing for their corrected BIC that has a heavier penalty.…”
Section: Real-world Examples and Performancesmentioning
confidence: 99%
See 1 more Smart Citation